Remaja Dan Krisis Etika : Bimbingan Nabi Untuk Generasi Z - Ria Maulidatur Rohma; Siti Lestari (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Gen Z is growing up in a digital age full of technological advancements and freedom of information. While this poses significant moral challenges, it also offers many positive opportunities. Modern teenagers often face conflicting norms, pressure from social media, and unhealthy environments. As a result, many of them lose their way, are easily influenced, and tend to ignore ethics in daily life. This crisis shows that the character building of teenagers has not yet reached the full level of success. Strong moral role models and guidance are needed to overcome it. Prophet Muhammad taught values such as honesty, responsibility, empathy, and compassion. These values are highly relevant to address the moral problems of modern adolescents. The onus is to convey these principles in a way that Generation Z can accept and understand using approaches that are communicative, innovative, and utilize digital media. In this article, we will discuss how the Prophet's guidance can be used as a moral compass for Gen Z teenagers in their daily lives. To revive the spirit of example in the lives of teenagers, the role of parents, teachers, communities and religious leaders is crucial. The teachings of the Prophet can strengthen the character of teenagers if applied correctly. They can also become a generation that is moral, critical and ready to face the challenges of the times without losing their identity.